Effect of whole blood transfusion in combination with plasmex-D–40 and hypertonic saline solution on acid-base and blood gas status of endotoxemic buffalo calves - SINGH, D V; SODHI, S P S (The Indian Journal of Animal Sciences, 2011)
Apparently healthy buffalo calves (15) aged between 4 months to 1 year were divided into 3 groups of 5 animals each, which were subjected to I/V infusion of E.coli endotoxin @ 5 μg/kg BW/h for 3 h and their acid-base and blood gas status was monitored. Group 1 animals, which were kept untreated and observed for 4 h after the endotoxin infusion revealed a nonsignificant decrease in arterial and venous pH along with significant decrease in arterial PO2 and increase in venous PO2. Endotoxin significantly decreased arterial O2 saturation while venous O2 saturation increased significantly. Mean arterial and venous PCO2, base buffer, base excess, ECF base excess and blood bicarbonate ion concentration varied nonsignificantly. Group 2 endotoxemic buffalo calves were infused I/V hypertonic saline solution (7.2% NaCl acq.) @ 4 ml/kg BW in 6.5 min followed by plasmex-D–40 (dextran–40) @ 10 ml/kg BW at a speed of 150 drops/min as one time infusion while group 3 animals were additionally given intravenous transfusion of whole blood @ 20 ml/kg. BW once only without any cross matching. The whole blood was collected 24 h before infusion from healthy male buffalo calves through jugular veinipuncture and stored in A.C.D. bottles. The group 2 endotoxemic buffalo calves had significantly higher arterial O2 saturation at 120 and 300 min of the start of endotoxin infusion while the animals of group 3 showed a significant decrease in venous blood pH, arterial and venous base buffer, base excess and ECF base excess. The mean arterial pH, arterial and venous PO2, PCO2, O2 saturation and blood bicarbonate was either close to or higher than pre-infusion values indicating the beneficial effect of whole blood transfusion in countering hypoxia which is invariably encountered during endotoxic shock.